A necessary diversity of perspectives in decision-making regarding deep seabed mining: implications for science, people, and the environment - Oliveira, Bruno; Fath, Brian D.; Galparsoro, Ibon; Guilhon, Maila (Frontiers in Sustainable Resource Management, 2025)
The transition from the current fossil fuel-based economy toward one that relies on renewable sources of energy allegedly will require a set of minerals for manufacturing batteries that store this energy and power electric devices. Deep seabed mining (DSM) is an economic activity that has the potential to fill these material requirements as it relies on collecting rich mineral resources from the bottom of the ocean. This activity brings enormous challenges to regulation and potentially irreversible impacts on a large scale. In addition, the seabed is considered a common heritage of humankind, and therefore, questions of distributions of burdens and profits also emerge. We build on the premise of social justice, legitimacy, and participatory processes to discuss six perspectives that should be considered while dealing with DSM. We claim that DSM should be seen through a wicked problem lens, acknowledging the limits of ignorance squared, inside a scientific paradigm open to the possibility of a post-normal science. Participation should center on recognizing plural rationalities, ensuring justice and capabilities, and actively including the global South. We conclude that DSM's legitimacy can be enhanced by following these six perspective guidelines.